Comparison of Tissue Factors in the Ontogenetic Aspects of Human Cholesteatoma - Kristaps Dambergs; Gunta Sumeraga; Māra Pilmane (Diagnostics, 2024)
Background: An acquired cholesteatoma is a benign but locally aggressive lesion in the middle ear. It is characterized by chronic inflammation and the destruction of surrounding bone. Therefore, the aim of this study was to compare defensins HβD-2 and HβD-4; pro- and anti-inflammatory cytokines IL-1α and IL-10; proliferation marker Ki-67; transcription factor NF-κβ; angiogenetic factor VEGF; Sonic hedgehog gene protein SHH; and remodeling factors MMP-2, MMP-9, TIMP-2, and TIMP-4 in adult and pediatric cholesteatoma tissue, and to compare these groups with control skin tissue. Methods: The study included 25 cholesteatoma tissue material samples from children, 25 from adults, and 7 deep external ear canal skin samples from cadavers. The tissues were stained immunohistochemically and evaluated using semi-quantitative methods. Nonparametric tests, such as the Kruskal–Wallis test and Spearman rank correlation, were used. Results: There were no statistically discernible differences between the adult and children groups when comparing the relative numbers of factor-positive cells. Conclusions: There are no histopathological differences between adult and children cholesteatoma tissues.